The Tale of Gyges and the King of Lydia - Smith, Kirby Flower (Gorgias Press, 2009)
Kirby Smith explores varying 5th and 4th century BC accounts of the life and demise of Gyges, best known from Herodotous' History
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: HISTORY / Ancient / General